Anti-neutrophil cytoplasmic antibodies (ANCA) in the clinical forms of leprosy - Freire, Beatriz F. A. [UNESP]; Ferraz, Alexandre A. F. [UNESP]; Nakayama, Edson; Ura, Somei; Queluz, Thais T. [UNESP] (My University, 1998)
Anti-neutrophil cytoplasmic antibodies (ANCA) are autoantibodies against enzymes present in primary granules of neutrophils and lysosomes of monocytes detected in systemic vasculitis and in other diseases, including infections. ANCA are markers of active Wegener granulomatosis, which presents some anatomo-pathologic and immune response features similar to those of leprosy. Thus, we raised the hypothesis that ANCA may be present in leprosy as markers specifically linked to the presence of vasculitis. The aim of this study was to determine the presence of ANCA in leprosy and its correlation with the clinical forms of the disease. Sera from 60 normal individuals and from 59 patients with different clinical forms of leprosy were studied. The patients were also allocated into reactional and nonreactional groups. By indirect immunofluorescence, ANCA were positive, an atypical pattern (A-ANCA), in 28.8% of the patient sera. A-ANCA predominated, although not significantly (p >0.05), in the reactional groups 37.9% vs 20.0%), and in those at the lepromatous pole (41.6% vs 20.0%). There was no correlation between ANCA positivity and either disease duration, disease activity, or therapeutic regimen (p >0.05). An interesting finding was the correlation between ANCA and gender: 94.1% of ANCA-positive patients were males (p <0.01), a feature that so far has not been reported in ANCA-related diseases and for which there is no explanation at the moment. By ELISA, the sera of the lepromatous leprosy patients did not show activity against either PR3, MPO, HLE, the most common ANCA antigens. Because A-ANCA are nonspecific, this finding requires further investigation for the determination of the responsible antigen(s). In conclusion, A-ANCA are present in 28.8% of leprosy patients but are not related to vasculitis in the erythema nodosum leprosum reaction and are not a marker of a specific clinical form.